Barriers and facilitators to interhospital transfer of acute pulmonary embolism: An inductive qualitative analysis - DeBerry, Jacob; Rali, Parth; McDaniel, Michael; Kabrhel, Christopher; Rosovsky, Rachel; Melamed, Roman; Friedman, Oren; Elwing, Jean M.; Balasubramanian, Vijay; Sahay, Sandeep; Bossone, Eduardo; Farmer, Mary Jo S.; et al. (Frontiers in Medicine, 2023)
Background Interhospital transfer (IHT) of patients with acute life-threatening pulmonary embolism (PE) is necessary to facilitate specialized care and access to advanced therapies. Our goal was to understand what barriers and facilitators may exist during this transfer process from the perspective of both receiving and referring physicians. Methods This qualitative descriptive study explored physician experience taking care of patients with life threatening PE. Subject matter expert physicians across several different specialties from academic and community United States hospitals participated in qualitative semi-structured interviews. Interview transcripts were subsequently analyzed using inductive qualitative description approach. Results Four major themes were identified as barriers that impede IHT among patients with life threatening PE. Inefficient communication which mainly pertained to difficulty when multiple points of contact were required to complete a transfer. Subjectivity in the indication for transfer which highlighted the importance of physicians understanding how to use standardized risk stratification tools and to properly triage these patients. Delays in data acquisition were identified in regards to both obtaining clinical information and imaging in a timely fashion. Operation barriers which included difficulty finding available beds for transfer and poor weather conditions inhibiting transportation. In contrast, two main facilitators to transfer were identified: good communication and reliance on colleagues and dedicated team for transferring and treating PE patients. Conclusion The most prominent themes identified as barriers to IHT for patients with acute life-threatening PE were: (1) inefficient communication, (2) subjectivity in the indication for transfer, (3) delays in data acquisition (imaging or clinical), and (4) operational barriers. Themes identified as facilitators that enable the transfer of patients were: (1) good communication and (2) a dedicated transfer team. The themes presented in our study are useful in identifying opportunities to optimize the IHT of patients with acute PE and improve patient care. These opportunities include instituting educational programs, streamlining the transfer process, and formulating a consensus statement to serve as a guideline regarding IHT of patients with acute PE.